Stochastic simulation of calcium microdomains in the vicinity of an L-type calcium channel - Wegner, Frederic von; Fink, Rainer (European biophysics journal, 2010)
We study numerically the local dynamics of the intracellular calcium concentration in the vicinity of a voltage- and calcium-dependent plasma membrane L-type calcium channel. To account for the low number of Ca2+ ions and buffer molecules present in sub-femtoliter volumes, we use an exact stochastic simulation algorithm including diffusion. We present a novel, unified simulation method that implements reaction-diffusion events of Ca2+ ions and buffer molecules, stochastic ion channel gating and channel conductance as a multivariate Markov process...